Work Motivation, Organizational Commitment, and Supervision Effects on Employee Performance in Wajo Regency Inspectorate - Asmiruddin Safar; Hasniaty Hasniaty; Sadly Abdul Djabar (Universitas Muhammadiyah Makassar, 2026)
Public sector institutions are increasingly required to demonstrate accountability and high performance, yet many regional oversight agencies continue to face declining output despite growing resource allocations. This gap between institutional mandate and actual performance highlights the need to examine internal organizational determinants of effectiveness. This study aimed to analyze the effects of work motivation, organizational commitment, and supervision on employee performance at the Regional Inspectorate Office of Wajo Regency. The research employed a quantitative explanatory design using a census approach, involving all 80 employees as respondents. Primary data were collected through structured questionnaires measured on a five-point Likert scale and analyzed using multiple linear regression after validity, reliability, and classical assumption tests were satisfied. The results showed that work motivation and supervision had positive and significant partial effects on employee performance, whereas organizational commitment did not demonstrate a statistically significant independent effect. Simultaneously, the three variables significantly influenced performance (F = 40.867, p < 0.001), explaining 61.7% of the variance in employee performance. Work motivation emerged as the strongest predictor, indicating that responsibility, recognition, and goal orientation were central drivers of improved outcomes. This study contributes to performance management literature by integrating psychological and structural factors within a single analytical framework in a regional public oversight context. The findings imply that strengthening motivational practices and enhancing supervisory quality are critical strategies for improving accountability and institutional effectiveness in local government organizations.